TOTAL QUALITY MENEJEMEN PENINGKATAN MUTU PENDIDIKAN ISLAM BERBASIS NILAI-NILAI KEISLAMAN - Yanuarti Pertiwi, Fauza; Zainuri, Ahmad; Gani Yasir , Muslim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Islamic education in Indonesia faces increasingly complex quality challenges amid the rapid currents of globalization and massive digital transformation. This study aims to examine the integration of Total Quality Management (TQM) with Islamic values as a comprehensive foundation for improving Islamic education quality, to analyze its implementation process in enhancing academic and non-academic service quality, and to identify its supporting and inhibiting factors. Employing a qualitative approach through library research methodology, all data were entirely derived from secondary sources comprising reputable national and international journals, scientific reference books, and educational policy documents analyzed critically using content analysis and critical discourse analysis. The findings reveal that TQM principles demonstrate remarkably strong epistemological compatibility with Islamic values such as amanah (integrity), itqan (professionalism), syūrā (deliberation), and ishlah (continuous improvement), generating an authentic and holistic quality management paradigm deeply rooted in Islamic scholarly tradition. TQM implementation grounded in Islamic values demonstrably enhances both academic and non-academic service quality significantly when driven by visionary leadership embodying Islamic character and actively engaging all stakeholders. The primary inhibiting factors include resistance to change, limited human resources, and insufficient conceptual understanding, while supporting factors encompass leadership commitment, human resource capacity building, and comprehensive stakeholder synergy. This research contributes to developing an applicable and sustainable TQM conceptual framework based on Islamic values for Islamic educational institutions throughout Indonesia.